Halothane does not directly interact with genome DNA of A549 cells - Topouzova-Hristova, T; Hazarosova, R; Bandreva, B; Stephanova, Elena (Folia biologica (Praha), 2007)
Although the inhalation anaesthetics are commonly used in clinical practice, their toxic effects on the lung cells have not yet been well studied. Previous studies indicated strong genotoxic effect of some inhalation anaesthetics, applied at clinically relevant concentrations. The aim of the present study was to assess the extent of DNA damage, nuclear abnormalities and possibility of human A549 cells to recover after treatment with halothane at lower concentrations. The data obtained demonstrate that even lower halothane concentrations could induce DNA damage although the anaesthetic does not interact directly with DNA. We have found that irreversible impairment of the cell genome is initiated at a concentration as low as 1.5 mM. Part of the cell population displays some characteristics of stress-induced apoptosis, defining this concentration as threshold for cell survival. We suggest that the intracellular signalling pathway triggers the toxic effects of halothane.
Keywords: halothan; nádorové buňky kultivované; nádorové buněčné linie; poškození DNA; Halothane; DNA Damage; finanční podpora výzkumu jako téma; Anesthetics, Inhalation; anestetika inhalační; Cell Line, Tumor; Tumor Cells, Cultured; Research Support as Topic